Inhibiting Glutamate Activity during Consolidation Suppresses Age-Related Long-Term Memory Impairment in Drosophila - Matsuno, Motomi (iScience, 2019)
In Drosophila, long-term memory (LTM) formation requires increases in glial gene expression. Klingon (Klg), a cell adhesion molecule expressed in both neurons and glia, induces expression of the glial transcription factor, Repo. However, glial signaling downstream of Repo has been unclear. Here we demonstrate that Repo increases expression of the glutamate transporter, EAAT1, and EAAT1 is required during consolidation of LTM. The expressions of Klg, Repo, and EAAT1 decrease upon aging, suggesting that age-related impairments in LTM are caused by dysfunction of the Klg-Repo-EAAT1 pathway. Supporting this idea, overexpression of Repo or EAAT1 rescues age-associated impairments in LTM. Pharmacological inhibition of glutamate activity during consolidation improves LTM in klg mutants and aged flies. Altogether, our results indicate that LTM formation requires glial-dependent inhibition of glutamate signaling during memory consolidation, and aging disrupts this process by inhibiting the Klg-Repo-EAAT1 pathway.